Chemical constituents from the calyces of Hibiscus Sabdariffa Linn and its a-Glucosidase inhibitory activity (IR) - Nadzirah Mohd Jauah (2018)
The purpose of this study was to investigate the chemical compounds from the calyces of Hibiscus sabdariffa Linn. and their α-glucosidase inhibitory activity. Samples were collected from Balik Pulau, Pulau Pinang. The total of three kilogram of samples were air dried at room temperature, grinded and serially extracted by solid liquid extraction technique using hexane, dichloromethane, methanol, ethanol and water. Compounds were isolated and purified by several chromatographic techniques. Their structures were elucidated with spectroscopic methods including Nuclear Magnetic Resonance (1D-NMR and 2D-NMR), Liquid Chromatography-Mass (LCMS) spectrometry, infrared (IR) spectroscopy, ultraviolet (UV) spectroscopy and compared with data reported in the literature. The α-glucosidase inhibitory activity on the crude extracts and pure compounds was conducted using α -glucosidase inhibitory assay. The finding of this phytochemical study has led to the isolation of seven pure compounds namely squalene, triglyceride fatty acid, ethyl stearate, 4-ethoxy-3-((ethoxycarbonyl)oxy)-4- oxobutanoic acid, 2-(1-ethoxy-4-methoxy-1,4-dioxobutan-2-yl)-1,5-dimethyl-3-(2- ethoxy-2-oxoethyl)-4-(2-methoxy-2-oxoethyl-3-(methoxycarbonyl)oxy)pentane-1,2,5 -tricarboxylate, 2-(2-ethoxy-2-oxoethyl)-1,5-dimethyl-3,4-bis-(2-methoxy-2-oxoethyl) -3-((methoxycarbonyl)oxy)pentane-1,2,5-tricarboxylate, 7-((1,5-dimethoxy-1,4-dioxo pentan-3yl)oxy)-3,11-bis(ethoxycarbonyl)-7-(3-methoxy-1-((methoxycarbonyl)oxy)-3 -oxopropyl)-5,9-dioxo-4,6,8,10-tetraoxatridecane-1,8-dioic acid along with two mixture compounds; mixture of stigmasterol with β-sitosterol and mixture of 3- hydroxy-4-oxopentanal with 5-hydroxy methylfurfural. The methanol crude extract showed the highest activity among other crude extracts towards α -glucosidase compared to acarbose and quercetin. In addition, the selected isolated compounds were not active against the α-glucosidase inhibitory activity. As a conclusion, inactive compounds which isolated from the calyces of Hibiscus sabdariffa Linn. did not show any α-glucosidase inhibitory activity. Implication of this study is it can be used as future references for phytochemical studies of this species to discover possible potential new drugs in pharmaceutical.